Building Literacy in Reading Foreign Language Books for Arabic Education Students - Aulia Mustika Ilmiani; Mukhtar I Miolo; Hunainah Hunainah; Ahmad Maghfurin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
Arabic Language Education study program students at IAIN Palangka Raya are prospective Arabic teachers who are prepared to have foreign language competence, but students still experience difficulties for various reasons. It makes all PBA Education study program lecturers simultaneously implement several activities in selected subjects to build literacy in reading books in foreign languages, both Arabic and English. This research aims to describe the process carried out by lecturers in building reading literacy of foreign language books, either Arabic or English, on PBA students in IAIN Palangka Raya. This research used the descriptive qualitative method. Data was collected from the interview, observation, and documentation, then further analyzed through data reduction, presentation, and verification, and validated with the triangulation method. The initial result of this research indicated that the lecturers do various activities to build students’ reading literacy, those are: introducing reading references in Arabic and English language, explaining the advantages of reading these references to the students, giving insight into reading steps, assigning students to review the references, and assisting students in composing and publishing scientific papers. This research suggests writing literacy for students and further research on different subjects and locations.